Answer

Verified

81.6k+ views

Hint: Whenever you get the questions of common tangent you have to write the equation of tangent to a given curve and then apply the condition of tangent for others. Here in case of parabola tangent means that equation has equal roots.so apply the condition and get a common tangent.

The equation of any tangent to ${y^2} = 4ax$ is $y = mx + \dfrac{a}{m}$,if it touches ${x^2} = 4ay$.

We know tangent touches at a single point so in case of parabola it is a quadratic equation and touches at single point means it has real and equal roots.

Then the equation ${x^2} = 4a\left( {mx + \dfrac{a}{m}} \right)$ has equal roots or, $m{x^2} - 4a{m^2}x - 4{a^2} = 0$ has equal roots.

We know condition of equal roots $

D = 0 \\

{\text{i}}{\text{.e }}{{\text{b}}^2} - 4ac = 0 \\ )$

$ \Rightarrow {b^2} = 16{a^2}{m^4},4ac = - 16{a^2}{m^4}$

$ \Rightarrow 16{a^2}{m^4} = - 16{a^2}{m^4} \Rightarrow m = - 1\left( {\because m \ne 0} \right)$

Putting $m = - 1$ in $y = mx + \dfrac{a}{m}$, we get $y = - x - a$

Or, $x + y + a = 0$

Hence option ${\text{A}}$ is correct.

Note: The key concept of solving questions of common tangent is first select a curve and write any general tangent to it and then apply the condition according to the second curve given in question. If the second curve is a circle then distance from center to tangent will be it’s radius but here in case of parabola equal roots will be conditioned.

The equation of any tangent to ${y^2} = 4ax$ is $y = mx + \dfrac{a}{m}$,if it touches ${x^2} = 4ay$.

We know tangent touches at a single point so in case of parabola it is a quadratic equation and touches at single point means it has real and equal roots.

Then the equation ${x^2} = 4a\left( {mx + \dfrac{a}{m}} \right)$ has equal roots or, $m{x^2} - 4a{m^2}x - 4{a^2} = 0$ has equal roots.

We know condition of equal roots $

D = 0 \\

{\text{i}}{\text{.e }}{{\text{b}}^2} - 4ac = 0 \\ )$

$ \Rightarrow {b^2} = 16{a^2}{m^4},4ac = - 16{a^2}{m^4}$

$ \Rightarrow 16{a^2}{m^4} = - 16{a^2}{m^4} \Rightarrow m = - 1\left( {\because m \ne 0} \right)$

Putting $m = - 1$ in $y = mx + \dfrac{a}{m}$, we get $y = - x - a$

Or, $x + y + a = 0$

Hence option ${\text{A}}$ is correct.

Note: The key concept of solving questions of common tangent is first select a curve and write any general tangent to it and then apply the condition according to the second curve given in question. If the second curve is a circle then distance from center to tangent will be it’s radius but here in case of parabola equal roots will be conditioned.

Recently Updated Pages

Name the scale on which the destructive energy of an class 11 physics JEE_Main

Write an article on the need and importance of sports class 10 english JEE_Main

Choose the exact meaning of the given idiomphrase The class 9 english JEE_Main

Choose the one which best expresses the meaning of class 9 english JEE_Main

What does a hydrometer consist of A A cylindrical stem class 9 physics JEE_Main

A motorcyclist of mass m is to negotiate a curve of class 9 physics JEE_Main

Other Pages

Electric field due to uniformly charged sphere class 12 physics JEE_Main

Differentiate between homogeneous and heterogeneous class 12 chemistry JEE_Main

Assertion The melting point Mn is more than that of class 11 chemistry JEE_Main

If a wire of resistance R is stretched to double of class 12 physics JEE_Main

A rope of 1 cm in diameter breaks if tension in it class 11 physics JEE_Main